Environmental Influences on Elite Sport Athletes Well Being: From Gold, Silver, and Bronze to Blue Green and Gold - Donnelly, Aoife A.; MacIntyre, Tadhg E.; O’Sullivan, Nollaig; Warrington, Giles; Harrison, Andrew J.; Igou, Eric R.; Jones, Marc; Gidlow, Chris; Brick, Noel; Lahart, Ian; Cloak, Ross; Lane, Andrew M. (Frontiers in Psychology, 2016)
This paper considers the environmental impact on well-being and performance in elite athletes during Olympic competition. The benefits of exercising in natural environments are recognised, but less is known about the effects on performance and health in elite athletes. Although some Olympic events take place in natural environments, the majority occur in the host city, usually a large densely populated area where low exposure to natural environments is compounded by exposure to high levels of air, water and noise pollution in the ambient environment. By combining methods and expertise from diverse but inter-related disciplines including environmental psychology, exercise physiology, biomechanics, environmental science and epidemiology, a transdisciplinary approach will facilitate a greater understanding of the effects of the environment on Olympic athletes.